2017
DOI: 10.1002/bin.1478
|View full text |Cite
|
Sign up to set email alerts
|

A simple intervention for stereotypical engagement with an augmentative alternative communicative device

Abstract: Although electronic devices may enhance the effectiveness of some behavioral interventions for children with autism spectrum disorders, such devices may also give rise to problem behavior such as repetitious button pressing (i.e., object stereotypy). Results of this study showed that a child with autism spectrum disorder only displayed high levels of object stereotypy on an iPad™ when presses generated auditory output. Subsequently, results showed that when the participant used the iPad™ without auditory outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite the potential limitation, we chose to collect data in this manner to capture the full effect of the treatment throughout the academic work session. Cook, Rapp, Burji, McHugh, and Nuta (2017) showed that access to an iPad™ increased multiple forms of stereotypy for a child with ASD. By keeping the HP-LS access time in the session, we ensured that stereotypy (both targeted and nontargeted) did not increase when the participant had access to the iPad™.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential limitation, we chose to collect data in this manner to capture the full effect of the treatment throughout the academic work session. Cook, Rapp, Burji, McHugh, and Nuta (2017) showed that access to an iPad™ increased multiple forms of stereotypy for a child with ASD. By keeping the HP-LS access time in the session, we ensured that stereotypy (both targeted and nontargeted) did not increase when the participant had access to the iPad™.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of the limited utility of the aforementioned treatment guidelines, Cook, Rapp, Burji, McHugh, and Nuta (2017) showed that a young male with ASD primarily used his communicative iPad to engage in object stereotypy when the auditory output was enabled. Conversely, when the auditory output was disabled (i.e., auditory stimulation for object stereotypy was not available), the participant used the communicative device to mand for various edible and tangible items.…”
mentioning
confidence: 99%
“…En ocasiones, las características de la aplicación pueden dar lugar a problemas de comportamiento, como presionar repetidamente botones cuando las pulsaciones generan un sonido, fomentando la velocidad y la respuesta aleatoria sin escuchar instrucciones. Este tipo de comportamiento se puede evitar configurando la salida auditiva (Cook et al, 2017) o poniendo la tableta a distancia hasta que se haya dado la instrucción, sobre todo al comienzo (Garnier, 2017).…”
Section: Aparición De Estereotipias O Conductas Repetitivasunclassified